Contribution of the Microhistorical Approach to Landscape and Settlement Archaeology: Some French Examples - Poirier Nicolas (Open Archaeology, 2024)
In this article, we study the contributions of the microhistorical approach to landscape and settlement archaeology in the French context. First, we outline the reception of microhistorical concepts in France. The micro-analytical scale allows a renewal of the questionings, of the approaches, and therefore of the vision of the studied societies. In the particular case of archaeological research on landscape and settlement, we argue that the microhistorical approach proposes the spatial micro-scale as a framework, but it must be surpassed by a comparative approach capable of discerning common trends and local particularities. This approach thus makes it possible to question major macro-historical questions that still lack clear and consensual answers, such as the modalities of transition between major historical phases, the nucleation of settlement into the medieval village, the extension of the finages and the possibility of agricultural growth in the early Middle Ages, or the modalities of management and exploitation of natural resources.